Jelmane To To Dogen: Genealogi Kekerasan dan Perjuangan Subaltern Bali - I Ngurah Suryawan (Kawalu: Journal of Local Culture, 2015)
The long history of violence and the making of Balinese cultural politics have marginalized the narratives of some segments of society who are excluded and defeated by power. Their small narratives lie in the periphery of the discourse of the preservation of Balinese cultural politics. In contrast, according to their testimony their power relation is captured in the history of violence and Balinese cultural construction. These subaltern groups have become victims, but subsequently struggle, and that with their own ways they have lived their own life in a hard way. The genealogy of violence has become the foundation of the establishment of Balinese culture inherited from colonial times. The genealogy is created in a number of events showing how the Balinese struggle to survive in the midst of terror. I Nyoman Nambreg and I Ketut Sorog are one of them. They become the only living eyewitnesses of the most tragical event in their life. This article argues that the construction of Balinese cultural politics has become the essence of culture. Therefore, by making use of subaltern studies, the narratives outside power with post–colonial perspectives will produce sharp and humanist analysis in observing the power of the genealogy of violence and Balinese cultural politics. Keywords: Genealogy of Violence, Violence, Subaltern, Cultural Politics, Survivor.